Influence of Lidocaine including Buprenorphine for Postoperative Analgesia after the Extraction of Mandibular Third Molars: A Randomized Controlled, Double-Blind, Split-Mouth Study - Nimrat K. Jawanda; Anand Shukla; Anupam Singh; Kalyana C. Pentapati; Srikanth Gadicherla (The Scientific World Journal)
Background. The presence of opioid receptors around the peripheral nerves offers the possibility of providing postoperative analgesia, thereby encouraging the study of the effect of opioids in combination with local anesthesia (LA). Studies have also reported the efficacy of peripherally administered opioids in achieving adequate analgesia in regions with inflammation. Applying the concept of peripheral opioid receptors, our study aimed to evaluate the effectiveness of opioid analgesia in managing postoperative pain. The split-mouth study was carried out to evaluate the efficacy of buprenorphine added to lidocaine 2% in providing postoperative analgesia after the surgical extraction of the impacted mandibular third molar. Materials and Methods. We conducted a randomized, double-blinded, split-mouth trial among 21 patients with impacted mandibular third molars bilaterally. In all patients, bilateral impacted mandibular third molars were extracted at different periods. The primary outcomes assessed were postoperative analgesia by the VAS score and the number of rescue analgesics consumed by patients at 24, 48, and 72 hours of interval via a questionnaire. Results. There was a statistical significant difference in postoperative analgesia duration at 24 (P = 0.012) and 48 hours (P = 0.024), respectively, between the test and control group. Even though the mean number of rescue analgesics consumed by the test group was less than that of the control group, no significant difference was seen. Conclusion. Buprenorphine added to lidocaine 2% showed a minimal decrease in the pain score and duration of postoperative analgesia with no difference in the frequency of rescue analgesics consumed between the test and control.